2009
DOI: 10.1021/je900009a
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of [Amim]Cl + Salt Aqueous Biphasic Systems and Its Application for [Amim]Cl Recovery

Abstract: In this study, binodal curves and tie line data of [Amim]Cl + salt (K 3 PO 4 , K 2 HPO 4 , K 2 CO 3 ) + water aqueous biphasic systems (ABS) were measured and correlated satisfactorily with the Merchuk equation and Othmer-Tobias and Bancroft equations, respectively. [Amim]Cl could be recovered from aqueous solutions using the ABS, and the recovery efficiency could reach 96.80 %. The recovery efficiency was influenced by the concentrations of the salts and their Homeister series: K 3 PO 4 > K 2 HPO 4 > K 2 CO 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 19 publications
2
98
0
1
Order By: Relevance
“…Rogers et al first reported the formation of an aqueous biphasic system based on [Bmim]Cl, water, and K 3 PO 4 (Gutowski et al, 2003). Subsequently, phase diagrams for a variety of IL/water/salt systems have been described, most of which are based on ILs containing imidazolium cations and chloride anions (Bridges et al, 2007;Deng et al, 2007Deng et al, , 2009Pei et al, 2007;Wu et al, 2008). The binodal curves for these systems can be fitted to the Merchuk equation, with tie-lines described by the Othmer-Tobias or Bancroft equations (Deng et al, 2007).…”
Section: Recovery and Recycle Of Ionic Liquidsmentioning
confidence: 99%
“…Rogers et al first reported the formation of an aqueous biphasic system based on [Bmim]Cl, water, and K 3 PO 4 (Gutowski et al, 2003). Subsequently, phase diagrams for a variety of IL/water/salt systems have been described, most of which are based on ILs containing imidazolium cations and chloride anions (Bridges et al, 2007;Deng et al, 2007Deng et al, , 2009Pei et al, 2007;Wu et al, 2008). The binodal curves for these systems can be fitted to the Merchuk equation, with tie-lines described by the Othmer-Tobias or Bancroft equations (Deng et al, 2007).…”
Section: Recovery and Recycle Of Ionic Liquidsmentioning
confidence: 99%
“…The resulting system consists of two immiscible phases, with the major component of these systems being essentially water. ATPS are environmentally safe, recyclable, economical viable, quick and scalable for application in industrial processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the phosphatebased inorganic salts were selected because they are important ions in biological systems [35]. K 3 PO 4 is indeed the most studied salt as a salting-out species [3,7,13,19,31,[36][37][38][39][40][41][42][43] followed by KH 2 PO 4 and KH 2 PO 4 /K 2 HPO 4 mixtures which are also frequently used at the biotechnological field [19,33,43,45,46].…”
Section: Introductionmentioning
confidence: 99%